Contribution of alluvial groundwater to the outflow of mountainous catchments. Issue 2 (5th February 2016) - Käser, Daniel; Hunkeler, Daniel
Abstract: Alluvial aquifers in mountainous regions cover typically a limited area. Their contribution to catchment storage and outflow is rarely isolated; alluvial groundwater discharge under gauging stations is generally assumed negligible; and hydrological models tend to lump alluvial storage with other units. The role of alluvial aquifers remains therefore unclear: can they contribute significantly to outflow when they cover a few percent of catchment area? Should they be considered a dynamic storage unit or merely a transmission zone? We address these issues based on the continuous monitoring of groundwater discharge, river discharge (one year), and aquifer storage (6 months) in the 6 km 2 alluvial system of a 194 km 2 catchment. River and groundwater outflow were measured jointly through "coupled gauging stations." The contribution of alluvial groundwater to outflow was highest at the outlet of a subcatchment (52 km 2 ), where subsurface discharge amounted to 15% of mean annual outflow, and 85% of outflow during the last week of a drought. In this period, alluvial‐aquifer depletion supported 75% of the subcatchment outflow and 35% of catchment outflow—thus 3% of the entire catchment supported a third of the outflow. Storage fluctuations occurred predominantly in the aquifer's upstream part, where heads varied over 6 m. Not only does this section act as a significant water source, but storage recovers also rapidly at the onset of precipitation. Storage dynamics were best conceptualized along the valley axis, rather than across the more conventional riparian‐channel transect. Overall the contribution of alluvial aquifers to catchment outflow deserves more attention. Key Points: Contributions of mountainous alluvial aquifers to total catchment outflow were quantified During low flow periods, subsurface outflow can dominate over stream flow Alluvial aquifers of limited spatial extent can release substantial amounts of water